Prothrombin Utilization Following Addition of Platelet Cofactor I Concentrates to Hemophilic Plasma - Frederic Johnson, J; Mammen, Eberhard F.; Seegers, Walter H. (Thrombosis and Haemostasis, 1959)
Prothrombin is utilized in hemophilia B blood when a platelet cofactor I concentrate is added. It is not well utilized when the same preparation is added to hemophilia B plasma, hemophilia A plasma, or hemophilia A blood. Platelet factor 3 concentrates did not promote prothrombin utilization. Mixtures of platelet cofactor I and platelet factor 3 (threone) give prothrombin utilization under all conditions tested in hemophilia A and B.